ANALISIS KEWENANGAN PEMERINTAH DESA DALAM BIDANG KEMASYARAKATAN: STUDI DI DESA TOKA KECAMATAN BULIK TIMUR KABUPATEN LAMANDAU - Ambri Semet (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2016)
Results of the study are (1) the execution of the authorities of the Government of the village of Toka in the field of development could be said to be doing well, one of them empirically though the village of Toka is one of the villages that are a bit far from the District of the city, but according to the results of the interview with the head of the village and the surrounding communities say if their area could be said to have never experienced a serious thing about events that interfere with their village. Then one form of civic activities was coaching against the participation of the citizens. The form of Participation in the village of Toka researchers can see namely the participation of government directives and from Community initiatives itself clearly visible. However, in essence community involvement village of Toka is big enough in carrying out various activities of social mutual clearly still visible in the village. (2) the Government authority went on supporting Factors village of Toka is to Coaching against the BPD. Factors restricting implementation of the Government of the village is village of Toka Government does not attempt to establish coordination with the mengitensifkan and Binmas and Babinsa, especially in the peace and order of the villagers either from the election of the village chief or in terms of the construction of public security of the village of Toka. This mostly happens in rural areas, because of the large number of societies that still do not understand about the procedure of manufacture certificate, let alone land that the original owners were their parents who already have no land boundaries so that they have even mutual claimed by the other party.